Methodology for assessing the threat of emergency situations to economic objects (Eurasian Journal of History, Geography and Economics, 2022)
It is known that an emergency situation affects the objects of the economy and prevents its stable operation. It is possible to assess the expected risks and determine ways to reduce the negative consequences of these risks through the methodology of assessing the threat of emergency situations to economic objects. The article describes the basics of assessing the threat of emergency situations to economic objects. Emphasis is placed on the importance of indicators in the assessment of threats.